2019
DOI: 10.3390/ma12193263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silica Fume in Concrete on Mechanical Properties and Dynamic Behaviors under Impact Loading

Abstract: The effect of silica fume (SF) in concrete on mechanical properties and dynamic behaviors was experimentally studied by split Hopkinson pressure bar (SHPB) device with pulse shaping technique. Three series of concrete with 0, 12%, and 16% SF as a cement replacement by weight were produced firstly. Then the experimental procedure for dynamic tests of concrete specimens with SF under a high loading rate was presented. Considering the mechanical performance and behaviors of the concrete mixtures, those tests were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Moreover, the dynamic tensile strength of samples rose with the silica fume (SF) amount, as well as with strain rate. In addition, the strain rate sensitivity of concrete augmented with SF appeared to have increased in comparison to concrete without SF (see Figure 4) [67]. Table 1.…”
Section: Silica Fume (Sf)mentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, the dynamic tensile strength of samples rose with the silica fume (SF) amount, as well as with strain rate. In addition, the strain rate sensitivity of concrete augmented with SF appeared to have increased in comparison to concrete without SF (see Figure 4) [67]. Table 1.…”
Section: Silica Fume (Sf)mentioning
confidence: 92%
“…The proportion of concrete constituents with different SF levels by weight [67]. Tensile performance was investigated in another study, in which 3 different series of concrete samples (see Table 1) with 0 wt.%, 12 wt.% and 16 wt.% SF as a cement substitute were produced and tested [67]. The results indicated that SF added to concrete yielded superior mechanical properties under dynamic tensile loading.…”
Section: Silica Fume (Sf)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the use of this waste material in cement is important in concrete production not only for economic reasons [ 3 ] but also for technical ones [ 4 ]. Some investigations have been carried out to investigate the application of silica stone as aggregate [ 5 , 6 ]. Furthermore, many investigations have been done to study the effect of silica on concrete [ 7 ], waste glass [ 8 , 9 ], and glass powder [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SHPB and Kolsky bar technique are widely used to conduct the test of dynamic constitutive behaviors on concrete-like materials [18][19][20]. However, the validity of SHPB results highly depends on the assumptions of one-dimensional stress wave propagation and stress uniformity along the specimen length [14].…”
Section: Introductionmentioning
confidence: 99%